Nursing Student Experiences Regarding Safe Use of Electronic Health Records: A Pilot Study of the Safety and Assurance Factors for EHR Resilience Guides. Issue 1 (January 2017) - Whitt, Karen J.; Eden, Lacey; Merrill, Katreena Collette; Hughes, Mckenna
Abstract : Previous research has linked improper electronic health record configuration and use with adverse patient events. In response to this problem, the US Office of the National Coordinator for Health Information Technology developed the Safety and Assurance Factors for EHR Resilience guides to evaluate electronic health records for optimal use and safety features. During the course of their education, nursing students are exposed to a variety of clinical practice settings and electronic health records. This descriptive study evaluated 108 undergraduate and 51 graduate nursing students' ratings of electronic health record features and safe practices, as well as what they learned from utilizing the computerized provider order entry and clinician communication Safety and Assurance Factors for EHR Resilience guide checklists. More than 80% of the undergraduate and 70% of the graduate students reported that they experienced user problems with electronic health records in the past. More than 50% of the students felt that electronic health records contribute to adverse patient outcomes. Students reported that many of the features assessed were not fully implemented in their electronic health record. These findings highlight areas where electronic health records can be improved to optimize patient safety. The majority of students reported that utilizing the Safety and Assurance Factors for EHR Resilience guides increased their understanding of electronic health record features.